2020
DOI: 10.1089/cap.2019.0072
|View full text |Cite
|
Sign up to set email alerts
|

Indole Tryptophan Metabolism and Cytokine S100B in Children with Attention-Deficit/Hyperactivity Disorder: Daily Fluctuations, Responses to Methylphenidate, and Interrelationship with Depressive Symptomatology

Abstract: Background: Indole tryptophan metabolites (ITMs), mainly produced at the gastrointestinal level, participate in bidirectional gut-brain communication and have been implicated in neuropsychiatric pathologies, including attention-deficit/ hyperactivity disorder (ADHD). Method: A total of 179 children, 5-14 years of age, including a healthy control group (CG, n = 49), and 107 patients with ADHD participated in the study. The ADHD group was further subdivided into predominantly attention deficit (PAD) and predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
1
8
2
Order By: Relevance
“…When comparing S100B values between ADHD patients and controls, our results differed from the first studies presented by Oades et al [ 42 ] and later by our group [ 45 ], in which no significant differences were observed between participants with ADHD and healthy children; indeed, an inverse relationship was reported between peripheral S100B levels and ADHD symptoms [ 43 ]. According to this, Oades et al [ 42 ] supported that the glial damage occurring in ADHD should be differentiated from the one taking place in other neuroinflammatory-based processes, such as schizophrenia [ 33 , 34 , 65 ], depression [ 66 ] or Alzheimer’s disease [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…When comparing S100B values between ADHD patients and controls, our results differed from the first studies presented by Oades et al [ 42 ] and later by our group [ 45 ], in which no significant differences were observed between participants with ADHD and healthy children; indeed, an inverse relationship was reported between peripheral S100B levels and ADHD symptoms [ 43 ]. According to this, Oades et al [ 42 ] supported that the glial damage occurring in ADHD should be differentiated from the one taking place in other neuroinflammatory-based processes, such as schizophrenia [ 33 , 34 , 65 ], depression [ 66 ] or Alzheimer’s disease [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, a cross-sectional study conducted on school-aged children with heavy metal-related ADHD in China revealed a significantly positive correlation between serum S100B levels and ADHD-like symptoms, although the correlation proved negative for the inattention and hyperactivity/impulsivity indexes in the Conners’ rating scale for teachers [ 44 ]. The results obtained by our group in a further clinical trial agreed with Oades et al [ 42 ], as no significant differences in serum S100B levels between ADHD children and controls were found; nevertheless, we also revealed that patients with depressive symptoms were prone to show higher S100B levels [ 45 ]. Given the contradictory results obtained by the few studies measuring S100B in patients with ADHD, further exploration of the involvement of this protein in ADHD could help understand the pathophysiology of this disorder.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…This day/night difference was not seen in the healthy control group or at discharge time in the schizophrenia patients either (27). It has been documented that both ADHD and healthy control groups had higher serum S100B concentrations in the mornings than in the evenings (28). Considering all, it may E a r l y A c c e s s be concluded that whether this is related to a psychiatric disorder pathophysiology or S100B circadian rhythm remains unclear.…”
Section: Discussionmentioning
confidence: 84%